(untitled) (Research, Society and Development, 2021)
Objective: To report and describe the epidemiological situation of HIV / AIDS in Brazil, in the Central West (CW) region and in the Distrito Federal (DF) between 2008 and 2018. Methods: Observational and descriptive study using data from the HIV/AIDS 2019 Epidemiological Bulletin, from the Ministry of Health, referring to HIV/AIDS cases and deaths between 2008 and 2018. Results: In the last 10 years, the AIDS detection rate has fallen in Brazil (17.9%), in CW (4.4%) and in DF (25.8%). During this period, Brazil went from 6.2 to 5.3 deaths/100,000 inhabitants and in the CW from 5.3 to 4.7 deaths/100,000 inhab. In the whole period, the DF presented a mortality rate lower than the national, having showed the lowest rate (3.6/100,000 inhab.) in 2018. Conclusion: Decreases in the rate of AIDS detection and mortality coefficient are observed in Brazil, CW and DF.